Analysis of histone modifications in key cellular subpopulations in the context of azoospermia using spermatogenic single-cell RNA-seq data - Wang, Qiu; Yang, Hong; Li, Fang; Ge, Song; Ji, Ling; Li, Xiaofeng (Frontiers in Bioinformatics, 2025)
IntroductionThe molecular underpinnings of non-obstructive azoospermia (NOA), a severe form of male infertility characterized by the absence of sperm in the ejaculate, remain unclear.MethodsIn this study, we demonstrate the role of histone modifications within specific testicular cell subpopulations in NOA using single-cell RNA sequencing (scRNA-seq) data.ResultsBased on scRNA-seq analysis of the data acquired from the Gene Expression Omnibus (GSE149512), we identified nine distinct cell types and revealed significant compositional differences between the NOA and control testicular tissues. In contrast to the high prevalence of spermatogenic cells in the controls, endothelial, testicular interstitial, and vascular smooth muscle cells, as well as macrophages, were enriched in NOA. Furthermore, our analyses revealed considerable enrichment of histone modificationrelated genes in Leydig cells, peritubular myoid (PTM) cells, and macrophages in the NOA group. HDAC2, a pivotal regulator of histone acetylation, exhibited significant upregulation. Functional pathway analysis implicated these genes in critical biological processes, including nuclear transport, RNA splicing, and autophagy. We quantified the activity of histone modificationrelated genes using AUCell and identified distinct Leydig cell subpopulations characterized by unique marker genes and functional pathways, underscoring their dual roles in histone modification and spermatogenesis. Additionally, cellular communication analysis via CellChat demonstrated altered interaction dynamics across cell types in NOA, particularly in Leydig and PTM cells, which exhibited enhanced interactions alongside differential activation of the WNT and NOTCH signaling pathways.DiscussionThese findings suggest that aberrant histone modifications in specific cellular subpopulations may drive disease progression, highlighting potential targets for diagnostic and therapeutic strategies. This study offers novel insights into the molecular mechanisms of NOA and provides a basis for future research on advanced male reproductive health.